The Impact of Occupational Noise on Hypertension Risk: A Case-Control Study in Automobile Factory Personnel - Wu, Xiaomei; Li, Chaoxiu; Zhang, Xiaohong; Song, Yumeng; Zhao, Dan; Lan, YueYan; Zhou, Bo (Frontiers in Cardiovascular Medicine, 2022)
Abstract Background: Many epidemiological studies have investigated the relationship between occupational noise and hypertension, but with conflicting findings. This study aimed to assess the relationship between occupational noise exposure and the risk of hypertension. Methods: A case-control study was conducted to explore hypertension predictors, and then sensitivity analysis was performed based on propensity score matching (PSM). Data were collected from participants’ annual physical examinations and occupational noise exposure measurements. Odds ratios (ORs) and 95% confidence intervals (CIs) were estimated using logistic regression analysis. A restricted cubic spline (RCS) function was used to fit the dose-effect relationship. Results: 500 cases and 4,356 controls were included in the study. Multivariate logistic regression showed that an increase in the level of occupational noise (range 68-102 dB(A)) of 1 dB(A), corresponded to an increase in hypertension risk of 8.3% (OR: 1.083, 95% CI: 1.058-1.109). Compared to the first quartile, the risk of hypertension in the fourth quartile was 1.742 (95% CI: 1.313-2.310). After applying PSM to minimize bias, we obtained a population of 500 cases and 1000 controls. Noise level was significantly associated with the risk of hypertension. In addition, the RCS curve showed the risk of hypertension was relatively stable until a predicted noise level of around 80 dB(A) and then started to increase rapidly afterward (Pnonlinear = 0.002) Conclusions: Occupational noise exposure was significantly associated with hypertension risk and there was a positively correlated dose-response relationship.